SOSIALISASI KARAKTER ANAK JALANAN DALAM MEMBENTUK PANDANGAN BERPOLITIK - Salim, Hisyamuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2023)
Criminal acts and often occur in Indonesia. For example, the case of corruption in Indonesia, which is still a serious problem in Indonesia, requires firm handling and action for this case. In addition, there are many criminal cases such as theft, murder, obscenity, and others. The action is motivated by internal factors, namely from within the individual and external factors that are influenced by the surrounding environment. The type of research used is descriptive qualitative. Data was collected by using observation techniques, interviews with related parties, and documentation. The author's purpose in bringing up this topic is to introduce character development and cultivation so that criminal acts in Indonesia can be reduced and receive firm and fair attention. The focus of this discussion is on street children where they have less economy to get a proper education. Therefore, the introduction of this character is taught not only to those who are in school, but also to street children who have limitations in obtaining education. So that street children can avoid criminal acts and crimes, as well as prepare political views such as conveying about daring to express opinions, being honest, and daring to be responsible.